Thrombosed Large Distal Posterior Inferior Cerebellar Artery Aneurysm Mimicking an Infratentorial Ependymoma - Peter Yat Ming Woo; Natalie Man Wai Ko; Kwong Yau Chan (Case Reports in Neurological Medicine)
Large or giant intracranial aneurysms can simulate brain tumors clinically and radiologically by virtue of their progressive mass effect. Unlike aneurysms from alternative locations, those arising from the distal posterior inferior cerebellar artery (PICA) are uncommon. We report a patient who experienced progressive hemiparesis with magnetic resonance imaging findings suggestive of an infratentorial ependymoma. Intraoperatively, a thrombosed large aneurysm of the distal PICA was unexpectedly encountered. The aneurysm was clipped and the patient did not develop any permanent neurological deficit. This case illustrates the radiological nuances of large aneurysms and infratentorial ependymomas. Three-dimensional contrast-enhanced magnetic resonance angiography can be falsely negative and the importance of the “target” sign is emphasized. One should be cognizant of this possible diagnosis for patients with midline fourth ventricular lesions in order to reduce surgical risk.